The Diagnosis and Treatment of Paranasal Sinus Cysts (Eurasian Medical Research Periodical, 2023)
Chronic rhinosinusitis is one of the most common chronic diseases of the upper respiratory tract, occurring in people of different ages. Cysts of the upper jaw cavity are distinguished by the fact that they are common in chronic sinusitis. From the clinical point of view, it shrinks without symptoms and in 80% of cases it is a finding during X-ray examinations. Modern medical technologies make it possible to treat chronic sinusitis with minimal tissue damage. The purpose of the research is to improve and use modern approaches in the complex treatment of cysts of the nasal cavities. We conducted our research on 153 patients aged 18 to 75 years with cystic changes of the upper jaw, forehead and sinuses with a disease duration of 2 to 5 years. Diagnosis of patients was carried out by endoscopic examination of the nose, multispiral computer tomography of the nasal cavities, orthopantography, functional and immunological examinations of the nose, microbiocinosis detection examinations. 134 of the patients who participated in our study underwent surgery. The surgical operation was performed in two stages at the same time, in the first stage, the structure of the nasal cavity was corrected, and in the second stage, the surgical operation was carried out in the affected side of the nasal cavity. Our research revealed that the cysts of the nasal cavity are mainly found in the upper jaw cavity. In the surgical treatment of PNScysts, it is necessary to pay special attention to the structures of the nasal cavity, especially the ostiomeatal complex, and to eliminate them at the same time when pathological changes are detected